La construcción nacional del territorio de Guatemala, 1825-1934 - Taracena Arriola, Arturo (2002)
Reying of interpretation of old maps and discursive analysis of the decrees issued by various Guatemalan governments regalding territoriality, the authors put forth several explanations for the fragmentation of Guatemala's territory into numerous departments.